PENDUGAAN STATUS STOK DAN INDIKATOR BIOEKONOMI PERIKANAN KERAPU DI TELUK SALEH, NUSA TENGGARA BARAT: Estimating Stock Status and Bioeconomic Indicator of Grouper Fishery in the Saleh Bay Waters, West Nusa Tenggara Province - Efendi, Diding Sudira; Karyoto, Karyoto; Irawan, Andi; Priyadi, Hermawan Gatot; Misuari, Muhammad Nur; Mulyandari, Nunik (Bogor Agricultural University, 2023)
One of the challenges in managing small-scale fisheries with limited data is the need for indicators to estimate the stock status and the total allowable catch for sustainable utilization of fish resources. This study aims to estimate the stock status, catch, and optimal fishing effort of the grouper fishery in Saleh Bay, West Nusa Tenggara Province by using the Length-based Spawning Potential Ratio analysis, production surplus model, and bioeconomic approach. Based on the results of this study, it is known that Plectopomus leopardus and Epinephelus coioides are in overexploited condition, while Plectropomus maculatus is in fully exploited status. This study also shows that with a bioeconomic approach, optimal conditions for grouper fisheries in these waters are achieved when the catch is 3,862.1 tonnes per year. The results of this study underline the importance of maximum economic yield-based management as a framework for a fishing quota-based system as an additional instrument in implementing sustainable fishery management in the future. The success of applying the quota system and the total allowable effort is determined by the accuracy of the catch data of small vessels around Saleh Bay under regulatory provisions, supervision and effective law enforcement, the socio-cultural conditions of local communities and the level of compliance with regulations.Keywords: fishing effort, grouper, overfished, quota system.